Identifying the Dimensions and Components of Sciences Education based on an Interactive Approach with Emphasis on the Nature of Science - Narimanfar, Narges; Zarghami Hamrah, Saeid; Asadzadeh, Hasan (Iranian Journal of Educational Sociology, 2022)
Purpose: The using an interactive approach in sciences education can improve its learning. Therefore, the current research was conducted with the aim of identifying the dimensions and components of sciences education based on an interactive approach with an emphasis on the nature of science.Methodology: This study in terms of purpose was applied and in terms of implementation method was qualitative. The current research population was university students and teachers of basic sciences who were familiar with the subject, which number of 15 people of them were selected as a sample according to the principle of theoretical saturation and with the purposive sampling method. The data was collected by the in-depth semi-structured interview method and its validity was confirmed by the triangulation method and its reliability was obtained by the agreement coefficient method between two coders 0.86. The data were analyzed by open, axial and selective coding method in MAXQDA software.Findings: The findings showed that for sciences education based on an interactive approach with an emphasis on the nature of science were identified 48 concepts in 16 categories and 4 themes; So that 4 themes were included quality-orientation in the sciences education system (with 3 categories of quality evaluation in the educational system of formal education, efficiency of the educational system for science education and lack of effectiveness of science education programs in the formal education system), strategic management of the education system of formal education (with 6 categories of trust to abilities and plans of policymakers, institutionalizing the principles of science education, intra-group and institutional collectivism, developing the structure of an educational implementation system for logical thinking, keeping pace with global developments and designing science education programs for students), proposed solutions for designing the science education system based on the interactive approach (with 3 categories of students' participation in education, emphasis on strengthening the spirit of independence of students and logical education and its place in modern education) and challenges of the formal education system in the field of sciences education (with 4 categories of identity and its place of science in the educational system, argument-oriented and having a critical view, macro structure and institutional level of formal education and criticism to the educational system of current education structure in schools.Conclusion: Based on the results of the current research and the identified dimensions and components for sciences education based on an interactive approach with an emphasis on the nature of science, experts and planners of the educational system can take an effective step towards improving the sciences education based on an interactive approach by improving its dimensions and components.